2021
DOI: 10.1161/strokeaha.121.035045
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Coagulation and Inflammation in COVID-19–Associated Ischemic Stroke

Abstract: Background and Purpose: We sought to determine if biomarkers of inflammation and coagulation can help define coronavirus disease 2019 (COVID-19)–associated ischemic stroke as a novel acute ischemic stroke (AIS) subtype. Methods: We performed a machine learning cluster analysis of common biomarkers in patients admitted with severe acute respiratory syndrome coronavirus 2 to determine if any were associated with AIS. Findings were validated using aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…In COVID-19 patients with altered NfL and GFAP, values of these markers had normalized in all individuals at 6-month follow-up, suggesting that post-COVID-19 neurological sequelae may be not accompanied by ongoing brain injury ( 91 ). Inflammatory and coagulatory markers like D-dimer, LDH, erythrocyte sedimentation rate (ESR), and CRP were independently associated with the occurrence of ischemic stroke in COVID-19 ( 92 , 93 ), while higher age, diabetes mellitus, and hypertension were found not to be significant predictors of stroke in this population, despite being known predictors of non-COVID-19 stroke ( 93 ). Levels of lymphocytes, procalcitonin, and creatinine were higher in COVID-19 stroke patients ( 94 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 89%
“…In COVID-19 patients with altered NfL and GFAP, values of these markers had normalized in all individuals at 6-month follow-up, suggesting that post-COVID-19 neurological sequelae may be not accompanied by ongoing brain injury ( 91 ). Inflammatory and coagulatory markers like D-dimer, LDH, erythrocyte sedimentation rate (ESR), and CRP were independently associated with the occurrence of ischemic stroke in COVID-19 ( 92 , 93 ), while higher age, diabetes mellitus, and hypertension were found not to be significant predictors of stroke in this population, despite being known predictors of non-COVID-19 stroke ( 93 ). Levels of lymphocytes, procalcitonin, and creatinine were higher in COVID-19 stroke patients ( 94 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 89%
“… 5 Patients with COVID-19 at the highest risk of ischemic stroke appear to be those with a history of ischemic stroke, 26 possibly a history of diabetes 4 and other traditional stroke risk factors, 27 and higher serum d -dimer levels. 28 , 29 …”
Section: Stroke As a Complication Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…5 Patients with COVID-19 at the highest risk of ischemic stroke appear to be those with a history of ischemic stroke, 26 possibly a history of diabetes 4 and other traditional stroke risk factors, 27 and higher serum d-dimer levels. 28,29 Outcomes in strokes occurring in patients with COVID-19 also appear worse, in terms of initial stroke severity (compared with historical controls), 30 functional outcome at discharge (compared with contemporary and historical controls), 30,31 discharge destination (compared with historical controls), 32 and inpatient mortality (compared with both contemporary and historical controls). 4,[30][31][32][33] With regard to etiologic classification, patients with COVID-19-associated ischemic strokes have been shown to present with more embolic-appearing findings on neuroimaging.…”
Section: Ischemic Strokementioning
confidence: 99%
“…al demonstrated that higher admission NLR values are independent predictors of symptomatic intracranial hemorrhage and 3-month mortality in LVO patients treated with mechanical thrombectomy. 27 29 In an observational study of 60 patients with acute ischemic stroke, Lin et. al showed that patients with the SARS-Cov-2 virus had a higher NLR compared to those without infection.…”
Section: Discussionmentioning
confidence: 99%